(3LGeY GdHjGf Yf JChjd Bj GdbQBfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3Gdbhd ai JChjd bhdg YR hLd (B" (3eGRGZ GdHUQ heG WZi dbO QCi ef BjGJ QHg GdcHQi (B" (3bGd CHh LYaQ eG eGd HUQ eMeO aYOd jejfkG hTeGdkG s
(3BNQgG (B:s
(3jfJgi HJaSjQ bhdg JYGdi (B" (3Ef gPG dgh Mb Gdjbjf aSHM HGSe QHc GdYXje (B" (3Hbhdg hbhdg aSHM HJSejI QHc GdYXje HCSeGFg GdMSfi ced GdSaQ HMeO Gddg s
(3ef CKfGA JaSjQ ShQI GdfLe Edi BNQ GdhGbYI s
(3ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g`s
(3cJHJ Ydi Qb ZRGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs